Hemodynamic Patterns in Intrauterine Growth Restriction: The Role of Arterial and Venous Doppler Studies - Siddique, Ayesha Siddiqa; Memon, Najma Parveen; Shams, Amber; Khan, Ahmed Ali; Shahbaz, Tooba; Rasheed, Sajida (Indus Journal of Bioscience Research, 2025)
Intrauterine growth restriction (IUGR) is an essential obstetric disorder that endangers maternal and fetal health. This condition is mostly due to placental insufficiency, which results in poor nutrient and oxygen transport to the fetus. Doppler ultrasound mainly arterial and venous Doppler is being used more commonly as a diagnostic modality to assess the hemodynamic changes in IUGR. This review succinctly discusses the arterial and venous Doppler findings in IUGR, focusing on their pathophysiological background, their clinical relevance and their ability to predict adverse pregnancy outcomes. Through a review of the clinical trial, observational, and post-market surveillance literature, Doppler ultrasonography is described with regard to its utility in the management of IUGR and areas for future study to enhance the translation of Doppler technology into clinical practice are proposed. The review also discusses the combination of Doppler studies with other biomarkers to establish a well-rounded approach to the diagnosis and treatment of IUGR.